Validation of agile methodology as ideal software development process using Fuzzy-TOPSIS method. (June 2022) - Govil, Nikhil; Sharma, Ashish
Highlights: In this paper, the Fuzzy TOPSIS method has been applied to identify the most suitable SDLC model for software development in the present scenario. The work presented in the article computes the ranks and closeness coefficients of all the alternative SDLC models based on different criteria. Six widely accepted SDLC models were compared with their core features by applying fuzzy logic and decision support systems in the form of the Multi-Criteria Decision Making method. Five experienced decision-makers from software industries, assigned weights in linguistic terms to each alternative model against criteria. By applying the Fuzzy TOPSIS method, it is validated that Agile Methodology is an Ideal selection for software development processes. Abstract: Agile methodologies have been an emerging choice of software professionals for the past decade and a half. However, apart from this, some other SDLC models are also available for selection in front of software developers to develop any software. Usually, project managers select any of these models to develop software through their past experiences. There is no logical basis for this selection to be completely correct, as a result of which there is always a risk of software failure or over budget if an inappropriate model has opted. Keeping this problem of software industries in mind, an ideal SDLC model has been identified mathematically in this article. In this article, we applied the Fuzzy TOPSIS method that validates Agile software development as an ideal choice. We have taken a total of six software development processes that are being applied globally. Feedback from five experienced decision-makers has been taken in the form of linguistic terms and further converted into fuzzy values to perform the computation of the closeness coefficient rank of each experimented alternative software development process.